Genetic Confirmation of Mungbean (Vigna radiata) and Mashbean (Vigna mungo) Interspecific Recombinants using Molecular Markers - Abbas, Ghulam; Hameed, Amjad; Rizwan, Muhammad; Ahsan, Muhammad; Asghar, Muhammad J.; Iqbal, Nayyer (Frontiers in Plant Science, 2015)
The present study was conducted with the aim to investigate recombination between mungbean (female) and mashbean (male) interspecific crosses using molecular markers i.e., URP (Universal Rice Primers), RAPD (Random Amplified Polymorphic DNA) and SSR (Simple Sequence Repeats). As a first step parental screening was performed and polymorphic markers differentiating parent genotypes were identified. Recombinations were then confirmed through polymorphic DNA markers in many of the hybrids. The NM 2006 × Mash 88 was found to be most successful interspecific cross as many of true recombinants, confirmed by molecular markers, belonged to this cross combination. The SSR markers were more efficient in detecting genetic variability and recombinations with reference to specific chromosomes and particular loci, while SSR (RIS) and RAPD identified variability dispersed throughout the genome. The DNA based marker assisted approach provided evidence for genetic confirmation of mungbean and mashbean interspecific recombinants and escalated the authenticity of selection in mungbean improvement programme.